SKALA PENGUKURAN SHIFT KERJA, BEBAN KERJA, DAN PERSEPSI KESEHATAN SEBAGAI STRESSOR DENGAN FASILITAS MANAJEMEN UNTUK PENANGGULANGANNYA - Chie, Ho Hwi; Zuraida, Rida (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
Human circadian system causes employees on night shift are at risk of experiencing increasedÂ stress, increased workload. Additionally, they should face the consequences of different health conditionÂ compared to employees who work on a normal shift during the day. This paper discussed the size of stressÂ levels of employees who work in a night shift system based on (1) workload and (2) health condition, as wellÂ as (3) employeeâs biological, social, and psychological condition. Other studies have shown that supportÂ from company can help employees cope with stress. The support is like management facilities, such asÂ support from supervisor to subordinate, and training support to improve necessary skills. Thus, besides theÂ size of employee stress levels, this study also discusses the relation of company support as stressÂ management. The result is a measurement model of stress level obtained based on Likert scale of 5. In thisÂ model, work shift stressors are measured by self-perception of self-satisfaction by the work shift. ForÂ occupational health perception, SF-36 is used to measure self-perception of health quality. As for theÂ workload, the measurement of four resources at works using the scale of visuality, audiotory, cognitive, andÂ psycomotor. The implication shows that this stressor measurement scales need to be tested to see theÂ reliability and validity of the work environment in Indonesia, as well as to test the correlation between theÂ variables used with management facilities received by employees.